Pengembangan Kurikulum Berbasis Outcome-Based Education (OBE): Kajian Konseptual tentang Implementasi, Evaluasi, dan Continuous Improvement di Pendidikan Tinggi - Sri Wahyuni Bintang; M. Rafli Aditya; Inom Nasution (Islamic Education, 2026)
The transformation of education in the twenty-first century requires curriculum systems capable of producing graduates with competencies that are measurable, relevant, and responsive to societal and industrial needs. Outcome-Based Education (OBE) has been widely adopted as a curriculum framework in higher education to ensure that learning processes are aligned with expected graduate outcomes. However, previous studies have predominantly examined individual aspects of OBE implementation, such as curriculum design, assessment, or quality assurance, with limited attention to the integration of these components into a comprehensive continuous improvement system. This study aims to synthesize the existing literature and develop a conceptual framework for OBE-based curriculum development that integrates planning, implementation, evaluation, and continuous improvement. A qualitative library research approach was employed by reviewing scientific literature, educational policies, and national and international journal articles related to OBE. Data were analyzed using qualitative content analysis to identify recurring themes, implementation patterns, research gaps, and conceptual relationships. The synthesis indicates that effective OBE implementation depends on constructive alignment among graduate learning outcomes, course learning outcomes, teaching strategies, authentic assessment, and institutional quality assurance. The review also reveals that feedback-based curriculum refinement, educator competency development, and institutional governance remain underexplored despite their critical roles in sustaining OBE practices. Based on these findings, this study proposes an integrated conceptual model linking outcome formulation, learning implementation, authentic assessment, evaluation, and continuous quality improvement through a data-driven feedback cycle. The proposed framework provides a holistic reference for curriculum development and offers practical guidance for higher education institutions seeking to strengthen educational quality and produce globally competitive graduates through sustainable OBE implementation.